Hormonal and dietary influences on true fractional calcium absorption in women: role of obesity - Shapses, S. A. (2012)
SUMMARY: The goal in this study was to examine the hormonal and dietary predictors of true fractional Ca absorption (TFCA) in adult women and to determine whether TFCA differs due to body weight. Results showed that TFCA is higher in obese individuals and dietary fat, estradiol, and 1,25-dihydroxy vitamin D are the most significant positive predictors of TFCA in adult women. INTRODUCTION: Calcium absorption is an important determinant of calcium balance and is influenced by several factors. Previous studies have identified that age, intake of protein, fat and fiber, and hormones such as 1, 25-dihyroxyvitamin D (1,25(OH)(2)D(3)) influence absorption. The determinants of TFCA using the double isotope method, the gold standard estimate of absorption, have not been examined previously in adult women nor has the role of obesity been addressed. METHODS: In this study, we examined the hormonal and dietary predictors of TFCA in adult women with a wide range of age, body weights, and nutrient intake. TFCA was measured using dual stable isotope ((42)Ca and (43)Ca) technique. Serum was analyzed for bone-regulating hormones, and dietary information was obtained through food records. The independent dietary factors and hormonal predictors (25-hydroxyvitamin D, 1,25(OH)(2)D(3), parathyroid hormone, and estradiol) of TFCA were analyzed using multiple regression analysis. RESULTS: Two hundred twenty-nine women aged 54±11 years old (24–75 years) and with BMI of 31±7.0 kg/m(2) were eligible and were categorized into tertiles of body mass index (BMI) into leaner, overweight, and obese. In the entire group of women, total fat intake, estradiol, and 1,25 (OH)(2)D(3) are significant positive predictors (p<0.05). As expected, age is a significant negative predictor of TFCA (R(2)=26%). TFCA is higher in obese women compared to non-obese women (p<0.05). CONCLUSION: Together, these data show that dietary fat is the most significant positive predictor of TFCA which may have implications for dietary intake for non-obese individuals who are more likely to have lower and potentially compromised Ca absorption.